2021
DOI: 10.1097/aln.0000000000003681
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Procedural Determinants of Postoperative Pain Trajectories

Abstract: Background The primary goal of this study was to evaluate patterns in acute postoperative pain in a mixed surgical patient cohort with the hypothesis that there would be heterogeneity in these patterns. Methods This study included 360 patients from a mixed surgical cohort whose pain was measured across postoperative days 1 through 7. Pain was characterized using the Brief Pain Inventory. Primary analysis used group-based traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 52 publications
1
88
0
Order By: Relevance
“…We chose K=5 classes initially as this had been shown to be the number of pain trajectory classes during the first 7 days following similar surgeries. 14 Evaluating the number of latent classes from 1 to 7 in the working model was then performed and the favored number of latent classes chosen based on the lowest Bayesian information criteria. The optimal structure of the model from fixed to unrestricted random effects was then determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose K=5 classes initially as this had been shown to be the number of pain trajectory classes during the first 7 days following similar surgeries. 14 Evaluating the number of latent classes from 1 to 7 in the working model was then performed and the favored number of latent classes chosen based on the lowest Bayesian information criteria. The optimal structure of the model from fixed to unrestricted random effects was then determined.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using similar methods to the current study, Vasilopoulos et al evaluated pain trajectories in a mixed surgical cohort across days 1-7 following surgery. 14 Five distinct trajectories of pain were identified: low, moderate-to-low, moderate-to-high, and high pain over time. A fifth trajectory identified dramatically decreasing pain over time.…”
Section: Original Researchmentioning
confidence: 99%
“… the case of PPSP, the combination of certain gene polymorphisms and phenotypic factors has been associated with an increased risk. 17,[19][20][21] Additional opportunities related to a better understanding of genetics include evaluating the metabolism and action of opioids, 22 risk of substance use disorder, 3 and potentially advanced interventional therapies for common chronic diseases such as intervertebral disc pathologies. 24 We are also learning that treatment decisions related to pain management may have previously unrecognized and unanticipated long-term consequences.…”
Section: The Future Of Pain Medicinementioning
confidence: 99%
“…Previous larger studies (22,000 patients) suggest that 28% of patients still experience moderate-to-severe acute pain after surgery, 3 and higher pain trajectories have been associated with more frequent returns to the emergency department and readmission. 4 In this issue of Anesthesiology, Vasilopoulos et al 5 report their empiric discrimination of the postoperative pain trajectories of patients in the 7 days after undergoing major elective noncardiac surgery. The importance of looking at pain trajectory versus a single point in time or an average of pain scores over time (area under the curve) is that it represents a patient's pain experience over the duration of their care, graphically visualizing the time course of pain, including a sense of its stability and resolution, and allowing a more complete overall picture of analgesic benefit.…”
mentioning
confidence: 99%
“…The prospective and iterative approach taken by Vasilopoulos et al 5 aimed to cluster patients with similar patterns and identified five unique postoperative trajectories, which is distinct from most previous descriptions, which typically have discerned only two or three trajectories. Their concise, clinically relevant descriptions of each of these groups revealed that, similar to previous trajectory work, most of the groups were primarily defined by the pain intensity/severity (high, moderate-to-high, moderate-to-low, and low), with the exception of a single group with a vastly different temporal pattern (descending pain group).…”
mentioning
confidence: 99%